NOTARY'S RESPONSIBILITY FOR CANCELLATION OF THE CONTENTS OF SHARES SALE AND PURCHASE DEED THROUGH COURT RULING (STUDY OF SUPREME COURT DECISION NUMBER 188 PK/PDT/2020) Date 01 July 2020 - Syafa Nabilla; Hasim Purba; Burhan Sidabariba; Agustining (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Notary liability for the cancellation of the contents of the proforma share sale and purchase deed through a court decision caused by the existence of parties who do not have good faith who face the Notary because the shares are pretend (proforma), on the other hand of the notary are asked to use the principle of prudence and the principle of knowing their clients, but on the other hand notaries also need to get legal protection if they are able to prove that after applying the principle Prudence turns out to exist among parties who do not have good faith so as to harm other parties who also associate notaries as defendants to be held accountable for illegal acts, so this needs to be studied.The formulation of the problem that will be studied in this study is what is the responsibility of the Notary for the share sale and purchase deed that he makes and is canceled by the court? What is the legal protection for parties who are agreed to in the sale and purchase of shares due to the cancellation of the share sale and purchase deeded by the court? What is the legal analysis used by the judge in canceling the proforma share sale and purchase deed in the Supreme Court Decision Number 188 PK/PDT/2020? The research method used is juridical normative with a case approach by analyzing cases in Bekasi District Court Decision Number 334 / Pdt.G / 2014 / PN. BKS, Bandung High Court Decision Number: 467/PDT/2016/PT. BDG, Supreme Court Decision Number: 1681 K / Pdt / 2017 and Supreme Court Decision Number : 188 PK / Pdt / 2020. The data sources used are secondary data with primary, secondary, secondary legal materials. Data collection tools with library research, qualitative data analysis. The results showed that notaries had difficulty reaching out and detecting further related to the sale and purchase of proforma shares (pretend) considering that after carrying out the precautionary principle, it turned out that there was one party who did not have good faith and harmed the other party who sued in court and made the notary a defendant, but in the case of Bekasi District Court Decision Number 334 / Pdt.G / 2014 / PN. BKS, Bandung High Court Decision Number: 467/PDT/2016/PT. BDG, Supreme Court Decision Number: 1681 K / Pdt / 2017 and Supreme Court Decision Number: 188 PK / Pdt / 2020, Notaries who conducted Judicial Review are proven innocent and are not charged with rent responsibility even though the notarial deed they made must still be cancelled, considering that Notaries only make shares sale and purchase terms between the parties which turns out that one of the parties applies the sale and purchase of shares.